The usage CZT SPECT to assess myocardial blood flow and flow reserve in myocardial infarction with non-obstructive coronary arteries patients. (8th February 2021) - Maltseva, A; Mochula, A; Vorobyeva, D; Gulya, M; Ryabov, V; Zavadovsky, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Myocardial infarction (MI) with non-obstructive coronary arteries (MINOCA) is currently of interest in terms of a small amount of data related to myocardial perfusion, myocardial blood flow (MBF) and myocardial flow reserve (MFR). Purpose. To assess the severity of myocardial perfusion, MBF and MFR impairment in MINOCA patients in comparison to those with MI with obstructive coronary artery disease (MICAD) and non-obstructive stable coronary artery disease (SCAD). Methods. The study group comprised 40 patients (29 men, mean age 62.9 ± 10.7 years). 28 patients were admitted to the hospital due to the acute coronary syndrome. At admission all patients underwent invasive coronary angiography (ICA) and cardiac biomarkers – Creatine phosphokinase-MB (CPK-MB) and Troponin I (TnI) measurement. Two groups of patients were created based on ICA results: 1) MINOCA: with coronary artery stenosis <50%, n = 11; 2) MICAD: with coronary artery stenosis ≥50%, n = 17. SCAD patients group without obstructive atherosclerosis was retrospectively selected from the hospital database. All patients underwent dynamic SPECT on Cadmium-Zinc-Telluride (CZT) gamma camera with the assessment of semi-quantitative indexes of myocardial perfusion (SSS, SRS, SDS) and quantitative parameters (rest MBF (rMBF), stress MBF (sMBF) and MFR). Results. After 24 hours cardiospecific biomarkers levels in MINOCA group were significantly (p < 0.05) lower compared to MICAD group: CPK-MB 21.5 (13.7;45.0) vs. 94.4 (53.1;217.0) U/L; TnI 0.5 (0.1;3.3) vs. 9.8 (2.0;23.0) ng/ml. Standard myocardial perfusion indexes differed significantly (p < 0.05) among all three groups (except SDS between the first and second groups): MINOCA: SSS 5.0 (3.0;6.0), SDS 2.0 (1.0;3.0); MICAD: SSS 9.0 (5.0;13.0), SDS 3.0 (2, 0;5.0); SCAD: SSS 1.5 (0.5;2.0), SDS 0.0 (0.0;2.0). Moreover, sMBF and MFR differed significantly in all three groups of patients: MINOCA: sMBF 1.2 (0.8;1.7) ml/min/g, MFR 2.0 (1.2;2.4); MICAD: sMBF 0.7 (0.6;1.0) ml/min/g, MFR 1.2 (1.1;1.5); control group: sMBF 2.2 (2.1;2.3) ml/min/g, MFR 2.6 (2.5;2.8). In 7/11 (64%) of MINOCA patients the value of sMBF was ≤1.5 ml/min/g. In the MICAD group 16/17 (94%) had sMBF ≤1.5 ml/min/g and all SCAD patients had sMBF >1.5 ml/min/g. In 4/11 (36%) of MINOCA patients MFR values were less than 2; in MICAD group MFR < 2 was observed in 15/17 (88%) patients. Conclusion. MINOCA patients have more severe myocardial perfusion abnormalities, lower MBF and MFR compared to those with stable CAD. It means that MINOCA patients may have other reasons for reduced myocardial blood flow, such as endothelial dysfunction, thrombophilia, etc., despite the absence of obstructive coronary artery lesion. Further studies are needed to assess added diagnostic and prognostic value of CZT SPECT derived myocardial flow indexes in MINOCA patients.